2014
DOI: 10.1167/iovs.14-14234
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis of Tight Junctions Caveolin Nitrosylation Dependent Is Improved by Cocoa Via Opioid Receptor on RPE Cells in Diabetic Conditions

Abstract: The detrimental effects on TJs in ARPE-19 cells exposed to DM milieu occur through a CAV-1 S-nitrosylation-dependent endocytosis mechanism. High-polyphenol cocoa or EC exerts protective effects through DOR stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 60 publications
1
17
0
Order By: Relevance
“…Although it has received comparatively less attention, diabetes also affects RPE function and leads to outer retinal changes that impact on photoreceptor and choroidal integrity. RPE culture-based models and in vivo studies have demonstrated that high glucose exposure or diabetes causes nitrosative stress (98) and metabolic changes relating to polyol metabolism (99). In the context of DME, new perspectives consider the contribution of changes to the outer BRB (oBRB) formed by the RPE.…”
Section: The Neurovascular Unit: a Framework For Understanding Drmentioning
confidence: 99%
“…Although it has received comparatively less attention, diabetes also affects RPE function and leads to outer retinal changes that impact on photoreceptor and choroidal integrity. RPE culture-based models and in vivo studies have demonstrated that high glucose exposure or diabetes causes nitrosative stress (98) and metabolic changes relating to polyol metabolism (99). In the context of DME, new perspectives consider the contribution of changes to the outer BRB (oBRB) formed by the RPE.…”
Section: The Neurovascular Unit: a Framework For Understanding Drmentioning
confidence: 99%
“…Importantly, they also identify novel therapeutic targets with potential for drug development. Examples of retinal cells used for in vitro investigation of diabetic retinopathy are pericytes , retinal capillary endothelium (Bhatwadekar et al, 2009), retinal pigment epithelium (Garcia-Ramirez et al, 2011;Rosales et al, 2014b), Müller glia and microglia (Wang et al, 2007).…”
Section: Modelling Diabetic Retinopathymentioning
confidence: 99%
“…35 It is also involved in some cases in epithelial cells, such as TNF-␣induced occludin internalization in enterocytes 36 and in MDCK cells; 37 claudin-2, -3, -4, and -7 internalization in enterocytes; 38 coxsackievirusinduced internalization of occludin in Caco-2 cells; 39 Escherichia coli cytotoxic necrotizing factor-1 or IFN-␥ -and LIGHT (lymphotoxin-like inducible protein that competes with glycoprotein D for herpes virus entry on T cells)-mediated endocytosis of occludin in intestinal epithelial cells; 40,41 and high glucose-induced claudin-1 and occludin internalization in retinal pigment epithelial monolayers (Table 1). 42 Macropinocytosis is the invagination and ruffling of the cell membrane to form a pocket-like structure through the polymerization of actin filaments. 43 It forms a vesicle for large cargo (>1 m) and is mostly involved in the uptake of extracellular fluid and molecules.…”
Section: Endocytosis Pathways For Tj Proteinsmentioning
confidence: 99%